(untitled) (Bangladesh Journal of Microbiology, 2011)
Seventy samples of milk sweets including 30 samples of khoa, 10 samples of burfi, 10 samples of gulabjamun, 10 samples of kalakand and 10 samples of peda from local vendors, private manufacturers and organized dairies in and around Chennai, India were collected. The milk products were examined for microbial quality that includes enumeration of total viable bacteria, coliforms, phychrotrops, aerobic spore farmers, yeast and mould and isolation, identification of mould species were carried out. The results revealed that the bacterial count, yeast and mould count of local vendor’s samples were significantly (P<0.01) higher when compared to private manufacturers and organized dairies except psychrotrophic count in local and private vendor’s samples were identical. The total percentage of occurrence of Aspergillus sp. isolated from khoa samples was found to be the highest (63.08 per cent) followed by Penicillium sp. (17.38 per cent), Rhizopus sp. (10.86 per cent), Fusarium sp. (4.34 per cent) and Mucor sp (4.34 per cent). However, the total percentage of occurrence of Aspergillus sp isolated from khoa based milk sweet samples was also found to be the highest (70.90 per cent) followed by Penicillium sp. (15.11 per cent), Rhizopus sp. (9.30 per cent), Mucor sp. (3.48 per cent) and Fusarium sp. (1.16 per cent). The present study concluded that the khoa, khoa based sweets produced by the local vendors were inferior in quality as compared private and organized dairies. Key words: Khoa; milk sweets; bacteriological count; yeast and mould; different sources DOI: http://dx.doi.org/10.3329/bjm.v27i2.9168 BJM 2010; 27(2): 32-37